ANALISIS PENGARUH CITRA MEREK, KUALITAS LAYANAN, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA RESTORAN CEPAT SAJI KFC DI TENGGARONG - Purnamasari, Sarwindah; Wijayanti, Silvana Kardinar; Fahleti, Widya Hana (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2023)
The purpose of this study was to determine the effect of brand image, service quality and price on purchasing decisions at KFC fast food restaurants in Tenggarong. This type of research used in this research is expalanatory with a quantitative approach. The number of population in this study obtained an average of 486 buyers per day. So the researchers used sampling using the Slovin formula with a = 10%, the sample obtained was 83 respondents. The method used in sampling is non-propability sampling with the type of accidental sampling. Data collection techniques using a questionnaire using multiple linear regression analysis tools using SPSS version 22 software. The multiple linear regression equation obtained in this study is Y = 0.772 + 0.154X1 + 0.147X2 + 0.627X3. The results of this study are the brand image, service quality, and price either simultaneously or together or partially have a positive and significant effect on purchasing decisions at KFC fast food restaurants in Tenggarong. The price variable is the variable that has the most influence on purchasing decisions, seen from the t test results, the price variable has a t count of 7.377, which is greater than the other two variables. The resulting R square value is 0.695, this means that 69.5% of purchasing decisions are influenced by the variables of brand image, service quality and price, while the rest (100% - 69.5% = 30.5%) is influenced by other variables such as promotion and product quality.